1999
DOI: 10.1002/(sici)1096-8628(19991105)87:1<23::aid-ajmg5>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium of MTHFR genotypes 677C/T-1298A/C in the German population and association studies in probands with neural tube defects(NTD)

Abstract: A number of studies have demonstrated that the common polymorphism 677C-->T in the gene encoding 5, 10-methylenetetrahydrofolate reductase (MTHFR) leads to a thermolabile variant with decreased enzyme activity and to mildly elevated plasma homocysteine. 677TT homozygosity was shown to be more frequent in NTD probands compared with controls in some studies. Recently, another polymorphism, 1298A-->C, in the MTHFR gene was described and combined heterozygosity 677CT/1298AC was suggested to be an additional risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(32 citation statements)
references
References 26 publications
7
25
0
Order By: Relevance
“…Consistent with our previous work, our expanded sample set showed an increased frequency of MTHFR 677 TT homozygotes in cases compared to controls (Whitehead et al 1995;Shields et al 1999). Ours, like most studies, also found evidence of linkage disequilibrium between the MTHFR 1298A fi C and the 677C fi T alleles (van der Put et al 1998;Stegmann et al 1999;Barber et al 2000;Richter et al 2001). Consistent with previous reports (van der Put et al 1998;Richter et al 2001), we also observed increased frequency of combined MTHFR heterozygotes in NTD cases compared to controls, but further analysis did not reveal any evidence of combined MTHFR genotype effects in relation to NTD risk that could not be simply explained as a by-product of linkage disequilibrium.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our previous work, our expanded sample set showed an increased frequency of MTHFR 677 TT homozygotes in cases compared to controls (Whitehead et al 1995;Shields et al 1999). Ours, like most studies, also found evidence of linkage disequilibrium between the MTHFR 1298A fi C and the 677C fi T alleles (van der Put et al 1998;Stegmann et al 1999;Barber et al 2000;Richter et al 2001). Consistent with previous reports (van der Put et al 1998;Richter et al 2001), we also observed increased frequency of combined MTHFR heterozygotes in NTD cases compared to controls, but further analysis did not reveal any evidence of combined MTHFR genotype effects in relation to NTD risk that could not be simply explained as a by-product of linkage disequilibrium.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported an increased frequency of combined heterozygotes (MTHFR 677CT/1298AC) in NTD cases compared to controls (van der Put et al 1998;Richter et al 2001). Other studies, some with a relatively small sample size, show no association (Weisberg et al 1998;Stegmann et al 1999;Trembath et al 1999;Barber et al 2000;Volcik et al 2000). Only one study to date has shown a direct association of the 1298C allele with NTDs (De Marco et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Examination of the prevalences at the 677 locus indicated almost identical frequency of the 677T allele for the Quechua as a whole and the Aché. Within the Quechua populations, however, the group living at the highest altitude Stegmann et al (1999); 8. Rady et al (1999); 9.…”
Section: Methodsmentioning
confidence: 99%
“…The C allele is associated with decreased enzyme activity, although to a lesser extent than the C677T mutation; however, neither the homozygous nor the heterozygous state for the 1298 mutation is associated with the higher plasma homocysteine or lower plasma folate concentrations that appear in the homozygotes for the C677T mutation. Combined heterozygosity of the MTHFR 677 and 1298 variants has been reported to be more common in children with NTDs (van der Put et al 1998), although not all studies support this association (Stegmann et al 1999), and only a proportion of spina bifida cases are attributable to known MTHFR alleles (Botto & Yang, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that MTHFR C677T and A1298C are in linkage disequilibrium. 39,47,48 Rosenberg et al 49 investigated the linkage disequilibrium of the C677T, A1298C and 3 other intronic dimorphisms among white Israelis, Japanese and Ghanaian Africans and found that the 677T allele was associated with one haplotype, G-T-A-C, in white Israelis and Japanese homozygotes. Our results provide evidence for linkage disequilibrium between the C677T and A1298C polymorphisms and are the first to suggest that the 1793A allele is also in linkage disequilibrium with both C677T and A1298C polymorphisms.…”
Section: Table V -Stratification Analysis Of Variants In Mthfr Haplotmentioning
confidence: 99%